DETERMINING OF MODERN FRAMEWORKS SPEED FOR CREATING WEB-INTERFACES - БАШОВИЙ, В. М.; СТАЦЕНКО, В. В.; СТАЦЕНКО, Д. В. (Technologies and Engineering, 2023)
Purpose. Study of forming lists of interactive components speed by modern frameworks that are used to create web-interfaces. Methodology. Methods for describing and analyzing the effectiveness of software tools, methods and tools for researching web applications are used. Results. The most popular JavaScript frameworks that are used to create web interfaces have been identified. These include React, Angular and Vue frameworks. The time taken by the specified frameworks to perform operations on the list of interactive components is determined. It was found that the Angular framework showed the best results: the total time to perform the most complex operation (complete page generation) is 45% better than React and 44% better than Vue. It has been established that frameworks have different architectures, which can change the operating time in other applications. In particular, component removal rate testing showed that the Angular framework spends significantly less time in the Scripting phase than React and Vue, but much more in the rendering phase. This indicates a difference in the algorithms for preparing data for web-application elements. Scientific novelty. The results of the JavaScript frameworks speed study for creating web applications are presented. The operations execution time of forming interactive components lists, their modification and deletion is analyzed. Practical significance. The presented information allows making an informed choice of a framework for creating web-applications.